THE EFFECT OF HEALTH AND OHS PROGRAMS ON EMPLOYEE LOYALTY AT PT. PHE NSO - Anora, Ayu; Multazam, Muhammad (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the effect of occupational health and safety programs on employee loyalty at PT. PHE NSO. The background of this study is based on the importance of creating a safe and healthy work environment to build employee engagement and long-term loyalty to the company. This study uses a quantitative approach with multiple linear regression methods. The number of respondents was 71 people from the company's operational division. The results of the analysis show that partially, the occupational health program has a positive and significant effect on employee loyalty with a t-value = 4.717 and a significance of 0.000 (<0.05). Conversely, the occupational safety program does not have a significant effect on employee loyalty, with a t-value = -1.091 and a significance of 0.279 (>0.05). Simultaneously, both independent variables have a significant effect on employee loyalty, evidenced by the F-value = 7.932 and a significance of 0.000 (<0.05). However, the coefficient of determination (R Square) was only 0.047, meaning that the two variables were only able to explain 4.7% of the variation in employee loyalty, while the rest was influenced by other factors outside the model. Thus, companies are advised to strengthen the implementation of occupational health programs and evaluate the effectiveness of occupational safety programs to have a greater impact on increasing employee loyalty.